Ulcerative colitis complicated with Fournier’s gangrene: A case report - Irina Bondoc; Marius Zamfir; Mara Mardare; Andrei Văcărașu; Alin Burlacu; Leila Ali; Ariana Hudita; Bianca Galateanu; Octav Ginghină; Georgios Georgiadis; Charalampos Mamoulakis (Public Health and Toxicology)
Ulcerative colitis (UC) is a chronic immune-mediated inflammatory disorder affecting the colon, which displays an increasing incidence worldwide and is characterized by symptoms of rectal inflammation such as rectal bleeding, tenesmus and multiple stools daily. The diagnosis of UC is not easy to establish, therefor an overall interpretation of the clinical manifestations together with the results of the laboratory tests, lower gastrointestinal endoscopic examination (colonoscopy) and histopathology examination findings are advisable. The choice of therapy for ulcerative colitis is based on activity, severity and extension of lesions and may include oral, systemic and topic therapy, as well as surgery. Patients with ulcerative colitis are generally immunocompromised predisposed to opportunistic infections. We present the case of a male aged 70 years diagnosed with ulcerative colitis with insidious evolution under systemic treatment, complicated with Fournier’s gangrene which is a very rare complication of ulcerative colitis that should be kept in mind. A multidisciplinary approach including urologists and colorectal surgeons is the key to define best individualized management.